Pseudomitral stenosis due to a sterile mitral annular abscess echocardiographic features - Mokhbat, J. (1984)
Sterile abscesses of the mitral annulus are rare lesions that are usually asymptomatic. Antemortem diagnosis may be suspected in a patient with a well-circumscribed echo-dense mass in the anterior or posterior regions of the mitral annulus on 2-dimensional echocardiography. In contrast to the previously published cases, the abscess resulted in left-ventricular inflow obstruction that clinically and hemodynamically mimicked mitral valve stenosis.